The Nexus of CO2 emissions, energy consumption, economic growth, and trade-openness in WTO countries - Lars Sorge; Anne Neumann (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
This paper analyzes the dynamic relationship between CO2 emissions, energy consumption, GDP, and trade-openness from 1971 to 2013, based on the Environmental Kuznets Curve (EKC) hypothesis for 70 WTO countries. Using recently developed secondgeneration panel data methods, the empirical results support the EKC hypothesis for the high-, middle-, and lower-income panels used. Concerning the energy consumption and economic growth nexus, the causality results support the conversion hypothesis for the high-income panel, whereas the neutrality hypothesis holds for the lower- and middle-income panels. Based on the causality results, trade-openness does not positively impact CO2 emissions, GDP leads CO2 emissions, and trade-openness causes energy consumption within any income panel. The net effect of economic growth, however, could help to stabilize future CO2 emissions within any income panel.
Keywords: 330; environmental Kuznets Curve; CO2 emissions; energy consumption; economic growth; trade-openness; Granger causality; second-generation panel data methods